Antioxidant activity of egg whites from Indonesian chicken and duck eggs with addition of pineapple extracts - Cahyo, Budiman; Dewi, R. L.; Rafida, Razali; Arifin, M.; Wulandari, Z. (Faculty of Food Science & Technology, UPM., 2025)
Inherently, egg whites are known for their antioxidant properties due to the presence of various proteins, peptides, phenolic compounds, and flavonoids. Further, the antioxidant properties of egg whites are believed to be enhanced by the hydrolysis of proteases, which produces various antioxidant peptides. While numerous studies have explored the production of antioxidant peptides through the hydrolysis of egg white proteins using commercially available proteases, none have employed natural proteases derived from pineapple extract, particularly on egg whites from Indonesian poultry species. Therefore, the present work aimed to assess the antioxidant activity of egg whites from two Indonesian poultry species: Kampung chicken (KC) and Alabio duck (AD), following the addition of pineapple extract. Results revealed that the Haugh units of KC and AD were significantly different, accompanied by differences in their protein concentrations, with AD having a higher protein concentration than KC. Hydrolysis of KC and AD with bromelain-containing pineapple extracts at 0, 0.5, and 1% concentrations increased protein concentration and flavonoid content of the hydrolysates. This pattern was observed in both KC and AD, with varying magnitudes. Antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, which demonstrated that both KC and AD effectively reduced DPPH activity, with IC50 values of 433.47 μg/mL (AD) and 504.82 μg/mL (KC). These findings suggested that the hydrolysis of egg whites with pineapple extract significantly enhanced the antioxidant potential of the eggs.